Phytochemicals from the stem bark of Mesua hexapetala (Hook. F.) P.S. Ashton., Mesua beccariana (Baill.) Kosterm. and Garcinia mangostana Linn. and their biological activities - Karunakaran, Thiruventhan (2017)
Phytochemical constituents isolated from the Calophyllaceae andClusiaceae family of plants have gained impressive attention recently due to their amazing potencies in biological activities such as anti-inflammatory, cytotoxicity and anti-bacterial. Coumarins and xanthones discovered from this family have exhibited potent biological activities and some of these compounds have been proposed as lead compounds for drug discovery processes. Nitric oxide plays a vital role in the key molecular signaling constituent involved in inflammatory processes and mass production of NO is one of the main factors that contribute towards chronic degenerative diseases such as cancer and arthritis. It is necessary to find an alternative sources from natural products such as plants as its offer greater hope in the identification of bioactive compounds, less adverse effects and their development into drugs for the treatment of inflammatory diseases. Phytochemical studies such as extraction, isolation and structure elucidation of the isolated compounds with the aid FTIR, GCMS, HRESIMS and NMR were performed on the stem bark of two selected species from the family of Calophyllaceae which are Mesua hexapetala and Mesua beccariana as well on the stem bark of species from the Clusiaceae family which is Garcinia mangostana afforded twenty secondary metabolites, three of which were identified as new compounds. Phytochemical investigation on the stem bark of Mesua hexapetala yielded one new coumarin derivative, hexapetarin (143) together with 1,3,7-trihydroxy-2,4-di (3-methyl-2-butenyl)xanthone (144), trapezifolixanthone (96), cudraxanthone G ( 19), stigmasterol (7), β-sitosterol (65) and γ-sitosterol (145). These findings are considered novel as no previous reports nor research have been conducted on Mesua hexapetala. Meanwhile, from the stem bark of Mesua beccariana, a new xanthone derivative, beccarixanthone T (146) and a new coumarin derivative, beccamarin T (147) were successfully isolated together with mesuarianone (1), mesuasinone (2), 1,5-dihydroxyxanthone (57), euxanthone (20) and four common triterpenoids, friedelin (8), 7, 65 and 145. The chemical constituents isolated from Garcinia mangostana were α-mangostin (14), β-mangostin (88), mangostenol (137), garcinone D (132) fuscaxanthone C (148), dulcisxanthone F (94) and 7. Moreover, the semi-synthesis reaction of β-mangostin which were acetylation and O-alkylation afforded six derivatives in which four are new derivatives, 6-monoacetate β-mangostin (149), 6-O-methyl β-mangostin (148), 6-O-benzyl β-mangostin (150), 6-O-n-hexyl β-mangostin (151), 6-O-n-butyl β-mangostin (152) and 6-O-sec-butyl β-mangostin (153). All extracted plant crude extracts, seven selected natural product compounds and four semi-synthetic derivatives of β-mangostin were evaluated for cell based cytotoxicity and nitric oxide inhibition assay. Nitric oxide inhibition activities indicated that four compounds 143, 144, 14 and 88 exhibited very significant activity towards inhibition of LPS/IFN-γ stimulated RAW 264.7 macrophages with IC50 value of 30.79 ± 2.68, 12.41 ± 0.89, 29.81 ± 0.77 and 11.72 ± 1.16 μM respectively. The ethyl acetate extract of G.mangostana and the n-hexane extract of M.hexapetalashowed very potent activities. Structure-activity relationship studies of pure compounds and semisynthetic derivatives of β-mangostin towards anti-inflammatory activity demonstrated the importance of hydroxyl groups in their structure which influence bioactivity. Anti-Bacillus tests were conducted on seven types of pure compounds - 145, 146, 147, 144, 14 and 88 as well as with all the plant extracts against four types Bacillus bacteria - Bacillus subtilis, B.cereus, B.megaterium and B.pumilus. Hexapetarin (145) showed potential anti-bacillus activities while the n-hexane and chloroform extract of M.hexapetala (MHH and MHC) gave good inhibitive activity towards these four bacteria. Thus, it can be summarized that the newly discovered coumarin derivative from M.hexapetala, hexapetarin (145), n-hexane crude extract of M.hexapetala and ethyl acetate crude extract of G.mangostana showed very significant nitric oxide inhibition and anti-Bacillus activity while compound 144, 14 and 88 portrayed very potent nitric oxide inhibition activities. These compounds can be further developed into anti-inflammatory agents.